Multi-technique approach for non destructive diagnostic of structural composite materials using bulk ultrasonic waves, guided waves, acoustic emission and infrared thermography. (November 2015) - Chaki, S.; Harizi, W.; Bourse, G.; Ourak, M.
Abstract: The damage phenomenon occurring in glass fiber reinforced polymer (GFRP) laminate is very complex; it is inherently an anisotropic, multi-source and multi-scale process. In the present work, a new non destructive testing (NDT) approach is suggested using, simultaneously, multiple techniques. These are bulk and guided ultrasonic waves, acoustic emission, passive and active infrared thermography, for evaluating mechanical damage occurring in GFRP laminate under uniaxial tensile tests. The principal result of this work, other than the success of each applied technique to evaluate the created damage in the material, is the possibility to effectively combine multiple NDT techniques in order to validate or to complete the diagnosis of the structural health of the materials.